Function of Barakka in Forming Social System (Phenomenology Study of Tariqah Pilgrim of Khalwatiah Samman in Maros District, South Sulawesi Province) - Sabiq, Muhammad; Syam, M. Basir; Tang, Mahmud; Radjab, Mansyur (International Journal of Psychosocial Rehabilitation, 2020)
This research aimed to identify, analyze and describe value of Barakka in Khalwatiah Samman Tariqah pilgrims as node point of a value which forms a systemic system of social life. Method used in this research was phenomenology approach conducted in Maros District, South Sulawesi Province in 2019. Data source were from primary data obtained through observation, documentation and in-depth interview with informants; khalifah (leader) and sanamangaji (students). Data were also from secondary data in form of book, journal, etc. The results showed that Barakka meant success and self-development. Thus, its symbolic presence was always awaited by every believer in accompanying himself, his business or work and his actions (actions). mattarima barakka people (people who obtain blessing) felt an inner atmosphere as a holy man who manifested in social interaction. Khalifah and sanamangaji should have function as central role in forming social system because they had understanding, experience and and ability to make barakka as a good value in life and better development of of individual and community.